Branchinecta gaini Daday, 1910 (Branchiopoda, Anostraca) as a bioindicator of oligotrophic and low conductivity shallow ponds in southern Chilean Patagonia (Crustaceana, 2012)
The south of Patagonia is characterized by its semi-arid weather and numerous small, temporary and permanent shallow ponds. The aquatic crustaceans of these water bodies are characterized by their endemism and species richness. The present study was done in the surroundings of Punta Arenas (53°S, Chile), and included six shallow ponds. Samples for conductivity, total dissolved solids, chlorophyll, and crustacean zooplankton as well as littoral species of crustacea were collected. Our study revealed that Branchinecta gaini Daday, 1910 occurred at low conductivity (0.55 mS/cm), and low total dissolved solids (0.28 g/l) and chlorophyll (2.70 μg/l) concentrations, such compared to sites without fairy shrimp populations, that had significantly high conductivity (3.58 mS/cm), and high total dissolved solids (1.80 mg/l) and chlorophyll (12.80 μg/l) concentrations. The results partially agree with the first descriptions of Patagonian water bodies that indicated the presence of fairy shrimps in low conductivity waters. The observations of the presence of B. gaini and other associated microcrustaceans are similar to descriptions of unpolluted water bodies in Antarctica, and those results would support the observations of the present paper. Other reports on fairy shrimp habitats mentioned a wide range of both salinity and trophic status. Other ecological and biogeographical topics on fairy shrimps are also discussed.